Reinforcement Pendidikan Islam melalui Program Gerbang Salam di Pamekasan - supandi, supandi; M. Sahibudin; Moh. Wardi; Ismail (State Islamic Institute of Madura, 2021)
What we mean by Islamic education is the implementation of educational activities carried out in the implementation of education in general, namely formal and non-formal Islamic education or community-based Islamic education based on the Islamic Community Development Movement program which was later termed (Gerbang Salam) which was carried out in Pamekasan Regency. The term